A capacity framework for strengthening science, education and practice of scaling innovation - Schut, Marc; Ronchi, L.; Dror, Iddo; Dahl, H.; Girvetz, Evan Hartunian; Hanke-Louw, N.; Hanna, E.; Kilwinger, Fleur B.M.; Nortje, K.; Thierfelder, Christian L.; Mugambi, S.; Leeuwis, C. (Wageningen University & Research, 2023)
This concept note is developed by the CGIAR Initiative for Diversification in East and Southern Africa (Ukama Ustawi). It highlights the significance of strengthening capacity in the science and practice of scaling innovation. The lack of a comprehensive and realistic understanding of innovation and scaling processes, coupled with limited scaling knowledge and capacity across individual, organizational and system levels hinder the effective scaling of innovations. Consequently, many promising initiatives fail to reach their full potential and address systemic issues at scale.